Hi-tech seed potato production system - Buckseth, Tanuja; Singh, Rajesh K; Sharma, Ashwani K; Tiwari, J K; Chakrabarti, S K (Indian Horticulture, 2020)
Seed potato production involving micro-propagation (tissue culture) techniques can overcome many problems associated with the conventional multiplication system. The everlasting shortage of seed potatoes in most of the potato growing nations can be overcome through micropropagation techniques on account of faster rate of multiplication. Besides, rapid multiplication, disease freedom on account of multiplication of disease free mother stocks under controlled conditions followed by reduced number of field exposures as compared to conventional multiplication system is an added advantage of seed potato production through tissue culture techniques. Due to these numerous advantages, the new hi-tech system of seed potato production involving micro-propagation is finding favour among the seed potato entrepreneurs.